Alcohol consumption and colorectal cancer risk: A mendelian randomization study - Li, Yuwei; Ye, Ding; Zhou, Wenkai; Liu, Bin; Mao, Yingying; Sun, Xiaohui (Frontiers in Genetics, 2022)
Abstract Background Previous observational studies have provided inconsistent evidence for the association between alcohol consumption and the risk of colorectal cancer (CRC). To assess this potential causal effect, we performed bidirectional Mendelian randomization (MR) analysis. Methods We selected six single nucleotide polymorphisms (SNPs) as instrumental variables (IVs) associated with alcohol consumption (ever versus never drinker) and two SNPs representing the number of drinks per week from a genome-wide association study (GWAS) of the Japanese population. Summary data for CRC were obtained from a GWAS meta-analysis in the Japanese population of 6, 692 CRC cases and 27,178 controls. MR analysis was performed by the inverse-variance weighted (IVW) method primarily, supplemented with several sensitivity methods including the weighted median method, maximum likelihood method, MR pleiotropy residual sum and outlier (MR-PRESSO) test, MR-Egger regression, Causal Analysis Using Summary Effect estimates (CAUSE) method, as well as constrained maximum likelihood and model averaging and Bayesian information criterion (cML-MA-BIC) method. Multivariable Mendelian randomization (MMR) analyses were used to adjust for potential confounders. Reverse MR analyses were also performed to assess the potential causal effect of CRC on alcohol consumption. Results Genetically predicted alcohol consumption (ever versus never drinker) was positively associated with the risk of CRC (odds ratio (OR)=1.08, 95% confidence interval (CI): 1.05-1.12, P=1.51×10-5 by IVW). The number of alcoholic drinks per week was also associated with an increased risk of CRC (OR=1.39, 95%CI: 1.27-1.52, P=5.29×10-13). Sensitivity analysis yielded similar results. Reverse MR analyses found no evidence that CRC contributes to either ever drinkers (OR=1.00, 95%CI: 0.99-1.00, P=0.339 by IVW) or added number of drinks per week (OR=1.01, 95%CI: 0.98-1.05, P=0.545 by IVW). Conclusions Our study suggested a potential causal association between alcohol consumption and the risk of CRC among Asians. Reducing drinking may be beneficial to the prevention and management of CRC.